Functional exercise capacity and life habits of schoolchildren (Fisioterapia e Pesquisa, 2018)
This study investigated life habits that can influence the performance on the six-minute walk test (6MWT) in eutrophic and overweight children. Anthropometric evaluations were carried out, as well as the functional exercise capacity and the habits, and Lifestyle in Childhood and Adolescence (Evia, acronym in Portuguese) was assessed in public school children aged between eight and ten years. We assessed 247 students, 132 (53%) girls and 115 (47%) boys; of these, 96 (39%) students were overweight, and 151 (61%) were eutrophic children. The most frequent life habits among children were: to watch TV (95%), to study at home (87%) and to do household chores (86%). No correlation was found between the performance on the 6MWT and the number of sleep/night hours, and between the performance on the 6MWT and the commute to home-school. Sport practice and nutritional classification showed correlation with the performance on the 6MWT with r=0.1793; p=0.0047 and r=0.1280; p=0.0445, respectively, and the multiple linear regression showed they have a weak influence on the performance of the 6MWT with R2=0.03009; p=0.0063 and R2=0.02287; p=0.0174, respectively. We concluded that life habits with low energy expenditure, such as watching television and studying are frequent. The number of sleep/night hours and the commute to home-school showed no correlation with the functional exercise capacity, and the sport practice and nutrition classification influence, even if weakly, the performance on the 6MWT among children in the age group assessed.